2021
DOI: 10.1177/15579883211007277
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Periodontitis and Erectile Dysfunction: A Systematic Review and Meta-Analysis

Abstract: The objective of this study is to investigate the association between periodontitis (PD) and erectile dysfunction (ED). A systematic review and meta-analysis on data was extracted and conducted according to PRISMA. Relevant articles were selected from a literature search using MEDLINE, EMBASE, Scopus, Web of Science and CENTRAL from inception until August 2, 2020. Both randomized and nonrandomized controlled studies were included. Case reports, case series, nonsystematic reviews and trials published as abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…[ 59 ] Multiple studies have shown a reduction in TNF-α levels after successful periodontal treatment, and evident that significant higher plasma levels of TNF-α were associated with moderate to severe ED owing to their known effects on the vasculature. [ 60 , 61 ] Management of the oral biofilm and periodontal health can therefore have positive implications in management of ED.…”
Section: Erectile Dysfunction (Ed)mentioning
confidence: 99%
“…[ 59 ] Multiple studies have shown a reduction in TNF-α levels after successful periodontal treatment, and evident that significant higher plasma levels of TNF-α were associated with moderate to severe ED owing to their known effects on the vasculature. [ 60 , 61 ] Management of the oral biofilm and periodontal health can therefore have positive implications in management of ED.…”
Section: Erectile Dysfunction (Ed)mentioning
confidence: 99%
“…124,125 Multiple studies have reported a reduction in TNF-α levels after successful periodontal treatment, and it is evident that significantly higher plasma levels of TNF-α were associated with moderate to severe ED owing to their known effects on the vasculature. 126,127 Management of oral biofilm and periodontal health can therefore have positive implications in the management of ED.…”
Section: Erectile Dysfunction (Ed)mentioning
confidence: 99%
“…7 Indeed, Uppal et al 8 found an association between the presence of periodontitis and ED, and Oğuz et al 9 suggested chronic periodontitis as an additional risk factor for ED.In contrast, Sharma et al 10 did not find a significant association between ED and the presence of periodontitis. Furthermore, recent systematic reviews by Farook et al 11 and Lecaplain et al 12 showed an association between periodontitis and ED. However, the effect of confounding factors and recall bias remain major limitations to the studies considered in these reviews.…”
Section: Introductionmentioning
confidence: 98%